A EFFECTIVITY OF FLASHCARD LEARNING MEDIA TO MEMORIZE VOCABULARY IN JAPANESE LANGUAGE - Nalurita Pambayung Putri (SOSIOEDUKASI, 2021)
Foreign language development in globalization era has caused many foreign language subjects added to school curriculum, one of them is Japanese language. One of school who added Japanese language to their curriculum is SMA Muhammadiyah 2 Genteng. In the process of Japanese language learning, there are many problems faced by students, one of them is difficulty in memorizing Japanese vocabulary. The author carries out classroom action research with object of research is class 10th Language dan Culture using flashcard learning media. The result from the classroom action research that has been carried out are the ability to memorize Japanese vocabulary in subject Watashi no Kazoku significantly increased after being given treatment using flashcard media learning. Keyword: effectivity, learning media, Japanese language